Biodegradation, Biosorption of Phenanthrene and Its Trans-Membrane Transport by Massilia sp. WF1 and Phanerochaete chrysosporium - Gu, Haiping; Lou, Jun; Wang, Haizhen; Yang, Yu; Wu, Laosheng; Wu, Jianjun; Xu, Jianming (Frontiers in Microbiology, 2016)
Reducing phenanthrene (PHE) in the environment is critical to ecosystem and human health. Biodegradation, biosorption and the trans-membrane transport mechanism of PHE by a novel strain, Massilia sp. WF1, and an extensively researched model fungus, Phanerochaete chrysosporium (P. chrysosporium) were investigated in aqueous solutions. Results showed that the PHE residual concentration decreased with incubation time and the data fitted well to a first-order kinetic equation, and the t1/2 of PHE degradation by WF1, spores and mycelial pellets of P. chrysosporium were about 2 hours, 87 days, and 87 days, respectively. The biosorbed PHE was higher in P. Chrysosporium than that in WF1, and it increased after microorganisms were inactivated and inhibited, especially in mycelial pellets. The detected intracellular auto-fluorescence of PHE by two-photon excitation microscopy also proved that PHE indeed entered into the cells. Based on regression, the intracellular (Kdin) and extracellular (Kdout) dissipation rate constants of PHE by WF1 were higher than those by spores and mycelial pellets. In addition, the transport rate constant of PHE from outside solution into cells (KinS/Vout) for WF1 were higher than the efﬂux rate constant of PHE from cells to outside solution (KoutS/Vin), while the opposite phenomena were observed for spores and mycelial pellets. The amount of PHE that transported from outside solution into cells was attributed to the rapid degradation and active PHE efflux in the cells of WF1 and P. Chrysosporium, respectively. Besides, the results under the inhibition treatments of 4 °C, and the presence of sodium azide, colchicine and cytochalasin B demonstrated that a passive trans-membrane transport mechanism was involved in PHE entering into the cells of WF1 and P. Chrysosporium.